FLOUTING MAXIM TO CONVEY SOCIAL CRITICISM DONE BY ABDURRAHMIN ARSYAD IN STAND UP COMEDY SEASON 4 KOMPAS TV - Gasa, Robi Pati; Khasanah, Ismatul; Chojimah, Nurul (Jurnal Budaya, 2020)
This research aimed to investigate the maxim flouted and the reasons for conveying social criticism done by Abdurrahmin Arsyad in stand-up comedy season 4. This was a descriptive research with an observation method applied to collect data. The data were in the form of the utterances of Abdurrahim’s performance on stage, while the data source was taken from some videos of Abdurrahmin Arsyad’s.The results showed four types of maxim were flouted: quantity, quality, relevance, and manner maxims. The reasons for those flouted maxims were to amuse the audience.To indicate politeness in conveying criticism, Abdurrahim also chose metaphor, rhetoric question, and irony through humor way.